FAKTOR PENENTU PENGGUNAAN LAYANAN E-FILING PAJAK - Puspitaningrum, Talia Endah; Mindarti, Ceacilia Sri (Dinamika Akuntansi Keuangan dan Perbankan, 2023)
This research aims to understand the factors influencing demand for tax e-filing. Population as the object of the research is individual taxpayers in the city of Pati. Respondents taken for research through the 318 individual taxpayers. Technique data collection in this research using a questionnaire. The Statistical Package for the Social Science (SPSS) version 26 is used to assist the process of data analysis in this research. The conclusion of this research is that security and privacy has no effect on the use of e-filing, perceived satisfaction has a positive and significant effect on the use of e-filing, experience has a positive and significant effect on the use of e-filing, and knowledge has a positive and significant effect on the use of e-filing.